STRATEGI PENURUNAN DOWNTIME DAN SETUP TIME PADA MESIN HEAT SEAL MENGGUNAKAN PENDEKATAN LEAN MAINTENANCE - Ong, Michelle Roselyn; Salomon, Lithrone Laricha; Kosasih, Wilson (Jurnal Mitra Teknik Industri, 2025)
The automotive battery manufacturing industry faces challenges in the effectiveness of its machine maintenance systems, particularly in the heat seal machine, which recorded the highest downtime with a total of 12,722 minutes and 434 occurrences from April 2024 to March 2025. This study aims to identify waste in breakdown maintenance activites, analyze the root causes, and provide improvement recommendations based on lean maintenance, The method used is Maintenance Value Stream Mapping (MVSM) to identify value-added (VA) and non-value-added (NVA) activities, and to calculate maintenance efficiency using indicators such as MTTO, MTTR, MTTY, and MMLT. In addition, root cause analysis is conducted using the five whys method and data collection through observation, interviews, and focus group discussion (FGD). The results show that maintenance efficiency is only 32.97% with NVA activities dominating at 67.03%. The identified types of waste include waiting, motion, process, and defects. The proposed improvements include the implementation of floation technicians, addition of trolleys, digitalization of the maintenance system using a Computerized Maintenance Management System (CMMS), and placement of toolboxes and equipment trolleys on the production floor. The implementation of the future state map shows an increase in efficiency to 38.22% and a reduction of NVA activities to 61.78%. These results indicate that the lean maintenance approach through systems.